Truck drivers project becoming a ware for prevention of the aids - Nascimento, Evania; Bueno, Sonia M. V.; Lopes, Erlon Cristian (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Background: Researchs in Brazil lcaded 10 truck drivers have proved thc vulnerably of thcse profcssionals involving risk situalions for HIV/Aids. So. several projects are being developed in order to sensitize them 10 lhe change of behavior,10 accepl safe sex. Objective: The truck drivers project of Faculdade de Enfermagem de Passos/UEMG. had as objective 10 involve 1he 1ruck drivers who ride on MG 050 freeway on reílccLion of possible behaviors that put them in risk of infection HIV/Aids. using as strategy lheir panicipation in lhe development of the informa1ion materiais. Methods: To lead the slrategies used in the Truck Drivers Project, we based on lhe research-action melhod. so this melhodology alows the interac1ion between lhe resarcher and the population involved, looking for soluction to the problems. Results: During the seven monlhs of the Truck Drivers Project we got to be in touch with 5.600 professionals that rode MO 050 freeway, alloting the truck driver kit and offering informations as individual levei in group, by means of lectures and discussions. Conclusion: The truck drivers were receptiveand they panicipated in ali programed activities, that make possible lhe appearence ofsentences that can be used as messages in other campaigns of directed prevention to these workers.